FACTORS THAT AFFECT FIRM VALUE IN MANUFACTURING FIRMS - Kurniawan, Rhenaldi Natanael; Susanti, Merry (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to obtain empirical evidence from the effect of profitability, leverage, liquidity, firm size, and activity ratio on firm value. Totals of 198 observational data originated from 66 manufacturing companies listed on Indonesia Stock Exchange (IDX) throughout 2018-2020. The sampling technique used in this research is purposive sampling. The hypothesis testing method in this research uses the multiple linear regression model. The multiple linear regression model estimation that suits this research is Fixed Effect Model (FEM). The statistical tool used for data processing in this research is EViews 12. This research uses Tobin's Q as a parameter to measure firm value. Based on the outcome of the processed data, profitability, leverage, and firm size all have significant effects on firm value, while liquidity and activity ratio both have insignificant effect on firm value.